The role of public export promotion in Finland Industry view of public export promotion in Southwest Finland - Weber, Konsta (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The role of the public export promotion in Finland needed more research. The part of the public sector export promotion in the overall export is significant. In an ever more global world not only the companies but also the counties compete against each other and the governments have an interest to boost their economy as much as they are able to. Every industrialized country has export promotion services in some form or another. In the 21st century the tendency has been the bundling of the services and this has also been done in Finland with Team Finland. The role and the efficiency of the services provided deserve more research. The research question of this study is: What is the role of the public export promotion services in Finland? The question is researched primary by expert interviews conducted for this study. The situation in Southwest Finland is studied from the viewpoint of the companies of the region by conducting a survey aimed to the successfully internationalized companies of the region and asking them on their views on the impact and role of public export services in their internationalization. The theory base is formed out of various export promotion studies, studies monitoring the effects of the promotion and theories of the internationalization process of companies. The primary material for the study are the three expert interviews conducted and the answers to the survey conducted. The research method in the first part is a constructive qualitative research. The research approach in the second part, where the views of the companies in Southwest Finland are studied, is quantitative. The study findings from the expert interviews: the aligning of the public export promotion done in Finland to the previous research and the addition of the role of the public sector in classical frameworks. The study findings from the survey: the utilizing of the public export promotion services is heavily delayed and the internationalizing companies start to utilize the services very late in their internationalization process, the average being 10,3 years from the beginning of the internationalization. Another central finding from the survey is that the successfully internationalized companies see the public export promotion services generally as highly beneficial but in the light of the answers the effect on their own company is not as significant. Concluding can be stated that the public export promotion is seen as beneficial, but the monitoring of the efficiency is complicated in the case of services. Getting the companies to start utilizing the services earlier in their internationalization needs attention from the service providers. By communicating the achieved results and benefits better to the potential users of the services the internationalization process of the companies could be accelerated